2006
DOI: 10.1007/s11214-006-9104-z
|View full text |Cite
|
Sign up to set email alerts
|

Ring Current Dynamics

Abstract: This chapter reviews the current understanding of ring current dynamics. The terrestrial ring current is an electric current flowing toroidally around the Earth, centered at the equatorial plane and at altitudes of ∼10,000 to 60,000 km. Enhancements in this current are responsible for global decreases in the Earth's surface magnetic field, which have been used to define geomagnetic storms. Intense geospace magnetic storms have severe effects on technological systems, such as disturbances or even permanent dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 70 publications
2
54
1
Order By: Relevance
“…The hourly Dst index values have been widely used as a proxy of the magnetospheric ring current strength and, consequently, the intensity of geospace magnetic storms, which are considered the most complex phenomenon of magnetospheric dynamics (Gonzalez et al, 1994;Daglis, 2006 …”
Section: Description Of the Datamentioning
confidence: 99%
“…The hourly Dst index values have been widely used as a proxy of the magnetospheric ring current strength and, consequently, the intensity of geospace magnetic storms, which are considered the most complex phenomenon of magnetospheric dynamics (Gonzalez et al, 1994;Daglis, 2006 …”
Section: Description Of the Datamentioning
confidence: 99%
“…Universality relates to the uncovering of a universal formula that describes with good approximation the same property on different systems (Zhou et al, 2006). For instance, de Arcangelis et al (2006) showed that the same empirical laws widely accepted in seismology also characterize, surprisingly, the size and time occurrence of solar flares. Recently, Balasis et al (2011a) provided evidence for universality in solar flare, magnetic storm and earthquake dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The presented similarities suggest that these apparently diverse phenomena may follow qualitatively similar physical mechanisms. For instance, de Arcangelis et al (2006) suggested that magnetic stress transfer in the solar corona plays the role of elastic stress redistribution on the Earths crust. We suggest that plasma pressure distribution in the inner magnetosphere could play the role of magnetic stress transfer in the solar corona and elastic stress redistribution on the Earths crust.…”
Section: Discussionmentioning
confidence: 99%
“…Long-lasting large southward IMF (Interplanetary Magnetic Field) enables energy transfer from the solar wind to the magnetosphere to enhance greatly through magnetic reconnection at dayside magnetopause. Large interplanetary electric fields (IEF) break into geospace, leading to dramatically enhanced and earthward shifted ring currents which cause a rapid decrease in the horizontal component of the geomagnetic field on the ground at low latitudes and characterize a geomagnetic storm development (Gonzalez et al, 1994;Gosling et al, 1991;Tsurutani et al, 1988;Daglis, 2006). Satellite observations show that storm time ring current mainly consists of ions with energy from tens to hundreds keV which drift westward over the equatorial area within 2-7 R E height.…”
Section: Introductionmentioning
confidence: 99%
“…particles newly input into ring current decreases, the convection boundary moves outside, cold ionospheric plasma refills the exhausted inner magnetosphere, then encounters with energy particles, and thus gives rise to plasma waves. Ring current ions loss is caused through 4 kinds of processes such as charge exchanges with neutral atoms, Coulomb collisions with plasma, pitch angle diffusion caused by waveparticle interaction, as well as drifting out of the dayside magnetopause (Daglis, 2006), and thus the ring current decays. This is the recovery phase of a magnetic storm.…”
Section: Introductionmentioning
confidence: 99%